Do social capital and the quality of institutions affect waste recycling?. (1st January 2023) - Argentiero, Amedeo; Chiarini, Bruno; Marzano, Elisabetta
Graphical abstract: Figures' sources: https://www.ilsole24ore.com/art/sostenibilita-e-rifiuti-passi-concreti-il-risveglio-green-ACAwyDp https://www.gograph.com/vector-clip-art/social-group.html https://www.kuirthiy.com/2022/08/if-you-build-bad-system-people-will-do.html Highlights: We develop a multivariate panel model for the Italian provinces (NUTS-3 level). Social capital and institutional quality positively affects waste recycling. Waste policies must be based on social cohesion and quality of institutions. Central and southern Italy needs social cohesion and efficient institutions. In the northern Italy, waste recycling is spurred only by social capital. Abstract: In a social capital framework, the quality of institutions and generalised social trust enhance attitudes towards disposal practices that are less environmentally invasive for the. This study aims to improve our empirical knowledge of this relationship through panel data models to show that waste recycling is affected by social capital and government effectiveness. The study uses Italian annual provincial data (NUTS-3 level) for 2004–2016 period to show that social capital and the quality of institutions are extremely important in determining waste recycling behavior. We find that both social capital and the quality of institutions, which act as 'substitutes for goods', increase waste recycling, although with different effects at the territorial level. In the southern and central areas, waste recycling needs to be spurred through policy interventions aimed at improving the quality of institutions, education and trust among citizens, whereas in northern Italy, social capital on its own is sufficient to enhance waste recycling. Hence, our results suggest that policies for waste recycling cannot be uncoupled from the promotion of social cohesion and institutional quality.